PENGARUH BIMBINGAN KELOMPOK TEKNIK SOSIODRAMA TERHADAP RESILIENSI SISWA MENGHADAPI BULLYING - Arinal Nurkhoirunnisa; Ummu Fitrotin Nursholihah (UIN Sunan Kalijaga Yogyakarta, 2026)
Bullying remains a big problem in schools and can hurt students' mental health, leads to anxiety, lower self-confidence, and trouble getting along with others. Building resilience is very important because it helps students deal with bullying in a better way. This study looked at how group guidance sessions that used the sociodrama method affected students' ability to handle bullying at MTs Nurul Ummah in Kotagede, Yogyakarta. A numbers-based method using a pre-experimental setup with one group that takes a test before and after the intervention was used. The participants were nine eighth-grade students who were chosen using purposive sampling because they had low or very low levels of resilience. Data were gathered using a bullying resilience scale based on the resilience factors suggested by Connor and Davidson. The data were analyzed using the Wilcoxon Signed Rank Test. The results showed a statistically significant difference between the scores before and after the test (Asymp.). Sig.(2-tailed) = 0.008, p < 0.05). Moreover, the average resilience score went up from 54.44 before the intervention to 63.33 after the intervention. These results show that using group guidance with the sociodrama method helps students become more resilient when dealing with bullying. Keywords: group guidance, sociodrama technique, resilience, bullying